2012
DOI: 10.1055/s-0031-1298172
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, Gastroprotective, and Cytotoxic Effects ofSideritis scardicaExtracts

Abstract: Sideritis scardica Griseb. (ironwort, mountain tea), an endemic plant of the Balkan Peninsula, has been used in traditional medicine in the treatment of gastrointestinal complaints, inflammation, and rheumatic disorders. This study aimed to evaluate its gastroprotective and anti-inflammatory activities. Besides, continuously increasing interest in assessing the role of the plant active constituents preventing the risk of cancer was a reason to make a detailed examination of the investigated ethanol, diethyl et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 34 publications
2
33
0
5
Order By: Relevance
“…Until now, there has been no comprehensive data on the toxicity of S. scardica except for one in vitro study, in which a significant dose-dependent decrease in proliferation was found in B16 (by 51.3%) and HL-60 (by 77.5%) cells treated with diethyl ether extract, and as speculated, phenolic compounds such as apigenin, luteolin, and their corresponding glycosides could be responsible for this effect [18]. These findings strongly advocated the need to further the toxicity evaluation of S. scardica , preferably using an in vivo experimental model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, there has been no comprehensive data on the toxicity of S. scardica except for one in vitro study, in which a significant dose-dependent decrease in proliferation was found in B16 (by 51.3%) and HL-60 (by 77.5%) cells treated with diethyl ether extract, and as speculated, phenolic compounds such as apigenin, luteolin, and their corresponding glycosides could be responsible for this effect [18]. These findings strongly advocated the need to further the toxicity evaluation of S. scardica , preferably using an in vivo experimental model.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts were analyzed for total polyphenols with a Folin–Ciocalteu method following guidelines of the European Pharmacopoeia [18] and for specific polyphenolic compounds (flavonoids, acteoside, caffeoylquinic acids) with a high-performance liquid chromatography (HPLC) method. For this purpose, a LunaR C18/2 column (Phenomenex, Torrance, CA, USA; 250 mm length, 4.6 mm inner diameter, 5 μm particle size) was used at 40 °C in a Shimadzu LC10 HPLC system (Shimadzu Deutschland GmbH, Duisburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakon 3h se razvija intenzivna fagocitna inflamacija sa velikim brojem neutrofila i otokom tkiva. Inhibicija edema predstavlja dokaz antiinflamatornog dejstva (158,159).…”
Section: Slika 310 Različita Ciljna Mesta Supstanci Koje Utiču Na Iunclassified
“…Brojna istraživanja su pokazala da mnoge aktivne komponente biljaka, pre svega flavonoidi i fenolkarbonske kiseline, sprečavaju infiltraciju neutrofila u inflamirano područje i uklanjaju slobodne radikale pa deluju antiinflamatorno. Flavonoidi mogu da inhibiraju 5-lipooksigenazu i ciklooksigenazu, a deluju i kao inhibitori PLA2, pa utiču na biosintetske puteve prostanoida (63,156,159).…”
Section: Antiinflamatorna Aktivnostunclassified